Pembelajaran Pakeliran Gaya Pokok II Inovatif dalam Program Merdeka Belajar Di Era Industri 4.0 - Andi Wicaksono; Jaka Rianto; Bagong Pujiono (Institut Seni Indonesia Surakarta, 2022)
This article discusses hoe the Pedalangan Department develops and implements Digital Learning Innovations in Pakeliran Gaya Pokok II (The Basic Style of Pakeliran) course. The purpose of this program is to provide convenience and freedom of learning in access that is no longer bound by distance, space, and time in the era of the sophisticated Information Technology (IT). In addition, it is an effort to respond to the Covid-19 pandemic condition which demands that learning in universities must be held online. Learning innovations in the development and implementation of digital innovations for Pakeliran Gaya Pokok II (Surakarta) include system, media, and content. The result of this program is the availability of digital learning media for Pakeliran Gaya Pokok II which is innovative and supports the independent learning programs in the industrial era 4.0.